A swelling termination tape for lithium battery and preparation method thereof

By adopting a multi-layer structure of lithium batteries, the problem of existing swelling tape falling off and dissolving in the lithium battery manufacturing process is solved, and the stable fixation of the battery cell and the improvement of battery performance are achieved.

CN118931400BActive Publication Date: 2025-04-04XIAMEN CHANGXINTAI TECHNOLOGY CO LTD

Patent Information

Application Number
CN202410975408.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2025-04-04
Estimated Expiration
2044-07-19

AI Technical Summary

Technical Problem

The existing swelling tape is prone to fall off during the manufacturing process of lithium batteries, resulting in loosening of the battery cell, affecting the service life and circulation performance of lithium batteries. At the same time, there is a problem of the dissolution of the tape in the electrolyte causing the diaphragm pore size to be blocked.

Method used

The swelling stop tape of lithium batteries consisting of release agent coating, polyurethane swelling coating, PET film layer and electrolytic solution-resistant polyurethane acrylic coating is used to expand at a high rate by absorbing the electrolyte, maintaining the three-dimensional structure and strength, and preventing the cell from falling off and the tape from dissolution.

Benefits of technology

The swelling termination tape can effectively fix the battery cell, increase the battery capacity and magnification, improve the battery's circulation performance, and enhance the impact resistance of lithium batteries, extend service life and safety factor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118931400B_ABST
    Figure CN118931400B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of swelling tapes, and in particular to a swelling termination tape for lithium batteries and a preparation method thereof. A swelling termination tape for lithium batteries, the swelling termination tape comprises, from bottom to top, a release agent coating, a polyurethane swelling coating, a PET film layer, and an electrolyte-resistant polyurethane acrylic coating, the release agent coating having a thickness of 0.5-1 μm, the polyurethane swelling coating having a thickness of 10-50 μm, the PET film layer having a thickness of 6-36 μm, and the electrolyte-resistant polyurethane acrylic coating having a thickness of 2-10 μm, wherein the electrolyte-resistant polyurethane acrylic coating, in terms of mass fractions, is prepared from raw materials comprising: 55-130 parts of modified polyurethane acrylate resin, 0.5-3 parts of amino resin curing agent, 0.5-5 parts of isocyanate curing agent, 0.5-2 parts of sulfonic acid, and 55-140 parts of solvent. The swelling termination tape of the present invention has the advantages of simple preparation process, strong high temperature resistance, high electrolyte resistance, high flame retardancy, etc., and can effectively enhance the impact resistance of lithium batteries, and extend the service life and safety factor of lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of swelling tapes, and in particular to a swelling termination tape for lithium batteries and a preparation method thereof. Background Art

[0002] Swelling tape is a kind of tape with synthetic rubber or resin as the base material, which has excellent oil surface adhesion, operability, expansion, filling, elasticity and good adhesion. With the continuous development of the new energy industry, lithium-ion batteries have received extensive attention due to their excellent performance. In the manufacturing process of lithium-ion batteries, some gaps are often reserved between the battery cell and the object, but the existence of the gap will cause the mutual movement between the battery cell and the shell, causing the battery to short-circuit and increase the battery size, which greatly increases the safety hazards during the use of the battery. In order to solve the above problems, the industry mainly uses expansion winding on the battery cell for fixing, but the existing swelling tape is wrapped around the battery cell in the manufacture of lithium batteries, and then tied into the shell with the swelling tape. After the electrolyte is injected and the charge and discharge cycle is carried out, the tape swells and falls off from the battery cell, and the battery cell becomes loose, affecting the service life of the lithium battery. There is also a problem that after the tape swells and falls off, the glue will dissolve in the electrolyte, causing the diaphragm aperture to be blocked, affecting the battery cycle performance. In addition, the heating of lithium-ion batteries can easily lead to spontaneous combustion, which in turn causes certain damage to the personal and property safety of users. Summary of the invention

[0003] In view of the shortcomings of the prior art, the present application provides a swelling termination tape for lithium batteries and a preparation method thereof. The swelling termination tape for lithium batteries of the present application has a simple preparation process, strong high temperature resistance and high electrolyte resistance, and can maintain a certain strength and shape in three dimensions by absorbing electrolyte to expand at a high rate, and will not fall off on the battery cell, nor will it be dissolved and fall off by the electrolyte, and plays a role in fixing and preventing the battery cell from loosening, increasing the battery capacity, rate and improving the battery cycle performance; the swelling termination tape is applied to lithium batteries, which can effectively enhance the impact resistance of lithium batteries, avoid relative movement of the shell and the battery cell when the lithium battery falls or is impacted, and cause the battery to fail, and extend the service life of the lithium battery and the safety factor of use.

[0004] In a first aspect, the present application provides a swelling termination tape for a lithium battery, which adopts the following technical solution:

[0005] A swelling termination tape for lithium batteries, the swelling termination tape comprising, from bottom to top, a release agent coating, a polyurethane swelling coating, a PET film layer and an electrolyte-resistant polyurethane acrylic coating, the release agent coating having a thickness of 0.5-1 μm, the polyurethane swelling coating having a thickness of 10-50 μm, the PET film layer having a thickness of 6-36 μm, and the electrolyte-resistant polyurethane acrylic coating having a thickness of 2-10 μm, wherein the electrolyte-resistant polyurethane acrylic coating is prepared from raw materials comprising, by weight, 55-130 parts of a modified polyurethane acrylate resin, 0.5-3 parts of an amino resin curing agent, 0.5-5 parts of an isocyanate curing agent, 0.5-2 parts of a sulfonic acid, and 55-140 parts of a solvent.

[0006] By adopting the above technical scheme, the release agent coating: the main function of this layer is to prevent the tape from sticking during storage or use, and ensure that the tape can be smoothly unfolded and used. The thickness of the release agent coating is controlled between 0.5-1μm, which is sufficient to provide the necessary anti-sticking effect without adversely affecting the overall performance. The polyurethane swelling coating: located above the release agent coating, mainly plays the role of absorbing electrolyte and swelling. Its thickness is 10-50μm, and it can form a three-dimensional structure after absorbing the electrolyte, filling the gap between the battery cell and the shell. The PET film layer: located above the polyurethane swelling coating, mainly plays a supporting and protective role. Its thickness is 6-36μm, with good high temperature resistance and chemical corrosion resistance, which can ensure the stability and reliability of the swelling termination tape during use. Electrolyte-resistant polyurethane acrylic coating: located at the top layer, mainly plays the role of electrolyte erosion resistance and flame retardancy. Its thickness is 2-10μm, and it is prepared from raw materials such as modified polyurethane acrylate resin, amino resin curing agent, isocyanate curing agent, sulfonic acid and solvent. The coating has excellent electrolyte resistance and flame retardant properties, can effectively prevent the electrolyte from corroding and dissolving the swelling termination tape, and improve the safety performance of the lithium battery. The swelling termination tape for lithium batteries of the present application, in its electrolyte-resistant polyurethane acrylic coating, the functions and synergistic effects of each component are as follows: 1. Modified polyurethane acrylate resin: as the main component of the coating, it provides good adhesion and chemical resistance, and at the same time has good flexibility and ductility, so that the coating can swell three-dimensionally after absorbing the electrolyte to form a three-dimensional structure with a certain strength. Amino resin curing agent: reacts with the modified polyurethane acrylate resin to increase the crosslinking density and hardness of the coating, and enhance the wear resistance and impact resistance of the coating. Isocyanate curing agent: reacts with the modified polyurethane acrylate resin to increase the crosslinking density and hardness of the coating, and enhance the wear resistance and impact resistance of the coating. Sulfonic acid: as a catalyst, it promotes the reaction of the amino resin curing agent and the isocyanate curing agent with the modified polyurethane acrylate resin, shortens the curing time, and improves production efficiency. Solvent: adjusts the viscosity and fluidity of the coating for easy coating and drying. In summary, the swelling termination tape in the present application achieves the characteristics of high temperature resistance, electrolyte corrosion resistance, high flame retardancy and excellent adsorption performance through the synergistic effect of various layers, which effectively enhances the impact resistance and safety factor of lithium batteries.

[0007] Preferably, the preparation method of the modified polyurethane acrylate resin is as follows: under nitrogen protection, polyether triol, polycaprolactone triol, hydroxyethyl methacrylate and dibutyltin dilaurate are uniformly mixed, the temperature is raised to 50-60° C., isophorone diisocyanate is added and reacted for 3-4 hours, and the temperature is then raised to 70-75° C., triphenyl phosphate is added and reacted for 2-3 hours to obtain the modified polyurethane acrylate resin.

[0008] By adopting the above technical scheme, the prepared modified polyurethane acrylate resin can effectively improve the swelling rate and flame retardancy of the electrolyte-resistant polyurethane acrylate coating. The triphenyl phosphate in the modified polyurethane acrylate resin not only introduces phosphorus elements but also introduces benzene ring structures, so that the swelling rate and flame retardancy of the electrolyte-resistant polyurethane acrylate coating are improved. The swelling termination tape prepared by the tight combination of the electrolyte-resistant polyurethane acrylate coating and the PET film layer can absorb the electrolyte and swell three-dimensionally, with a high swelling rate, and will not be dissolved by the electrolyte. It can be used to fill the gap between the lithium battery cell and the shell, and has excellent flame retardant properties, which can effectively enhance the impact resistance of the lithium battery, and prevent the relative movement of the shell and the cell when the lithium battery falls or is impacted, causing the battery to fail, thereby extending the service life of the lithium battery and the safety factor of use. The present application further compounds the modified polyurethane acrylate resin with modified silica, improves the adsorption performance of the tape, and solves the technical problem that the existing expansion adhesive has poor expansion effect in high-temperature electrolyte due to poor temperature resistance.

[0009] Preferably, the mass ratio of the polyether triol, polycaprolactone triol, hydroxyethyl methacrylate, dibutyltin dilaurate, isophorone diisocyanate and triphenyl phosphate is 35:17:23:3.5:23:3.6.

[0010] Preferably, the isocyanate curing agent is at least one of toluene diisocyanate and diphenylmethane diisocyanate.

[0011] Preferably, the solvent, by weight, comprises: 25-90 parts of isopropanol and 30-50 parts of N,N-dimethylformamide.

[0012] Preferably, the raw materials for preparing the electrolyte-resistant polyurethane acrylic coating further include, by weight: 5-6 parts of modified silicon dioxide.

[0013] Preferably, the method for preparing the modified silicon dioxide comprises the following steps:

[0014] S71. Dissolve 8 parts of succinic anhydride in 40-50 parts of N,N-dimethylformamide solution according to mass fractions, add 18 parts of γ-aminopropyltriethoxysilane, heat and stir at a water bath temperature of 73° C. for 2-3 hours to obtain a mixed solution A.

[0015] S72, dissolving 12 parts by mass of silicon dioxide having an average particle size of 10 nm in 50 parts of N,N-dimethylformamide solution to obtain a mixed solution B;

[0016] S73, adding the mixed solution B dropwise into the mixed solution A, and continuing to stir and react for 3 hours to obtain pretreated silica;

[0017] S74, mixing the pretreated silica with 10 parts of 2-methylimidazole and 8 parts of zinc nitrate hexahydrate, adding 140 parts of ethanol, and ultrasonically polymerizing in an 800 W water bath ultrasonic device for 3-4 hours, washing and drying the obtained product to obtain modified silica.

[0018] By adopting the above technical scheme, the role and coordination of the modified silica prepared in this application are mainly reflected in the following aspects: Increase adhesion: The modified silica increases the adhesion between the electrolyte-resistant polyurethane acrylic coating and the PET film layer, prolongs the service life of the swelling termination tape, and ensures that the swelling termination tape will not have residual glue when removed. Improve surface properties: The surface of unmodified silica contains hydroxyl groups, which easily absorbs moisture in the air, and often phase separation occurs when applied to organic materials. An organic coating layer is formed on the surface of the modified silica, which can effectively reduce the surface energy of silica and improve the surface properties of silica. Improve affinity: The modified silica increases the affinity of silica with organic materials, and enhances the strength, toughness, high temperature resistance and electrolyte resistance of the swelling termination tape. Improve adsorption performance: The modified polyurethane acrylate resin is compounded with the modified silica to improve the adsorption performance of the tape, solving the technical problem that the existing expansion glue has poor temperature resistance and poor expansion effect in high-temperature electrolyte. Enhanced lithium battery performance: The use of modified silica makes the swelling termination tape have better electrolyte and high temperature resistance, forming a three-dimensional structure with a certain strength, effectively filling the gap between the battery cell and the shell, and improving the impact resistance of the lithium battery. It prevents the relative movement of the shell and the battery cell when the lithium battery falls or is impacted, which may cause the battery to fail, thereby extending the service life of the lithium battery and the safety factor of use.

[0019] In a second aspect, the present application provides a method for preparing a swelling termination tape for a lithium battery, using the following technical solution:

[0020] As a general technical concept, the present application also provides a method for preparing the swelling termination tape for lithium batteries, comprising the following steps:

[0021] S81, dissolving 8 kg of thermoplastic polyurethane resin in 8 kg of N,N-dimethylformamide, and after the thermoplastic polyurethane resin is completely dissolved, adding 0.8 kg of toluene diisocyanate, stirring evenly, to obtain polyurethane glue;

[0022] S82, applying polyurethane glue onto the PET film surface, and forming a polyurethane swelling coating on the PET film after drying, to obtain a PET film coated with the polyurethane swelling coating;

[0023] S83, dissolving the modified polyurethane acrylate resin in a solvent according to the mass fractions, and after the modified polyurethane acrylate resin is completely dissolved, respectively adding an amino resin curing agent, an isocyanate curing agent and a sulfonic acid, stirring evenly, to obtain an electrolyte-resistant polyurethane acrylate glue;

[0024] S84. Apply electrolyte-resistant polyurethane acrylic glue to the release surface of the PET single-sided silicon release film, and after drying, form an electrolyte-resistant polyurethane acrylic coating on the PET single-sided silicon release film, and then laminate the electrolyte-resistant polyurethane acrylic coating to the PET surface of the PET film coated with a polyurethane swelling coating. After lamination, apply a layer of non-silicone release agent on the polyurethane swelling coating surface, and after drying, peel off the PET single-sided silicon release film, and then perform aging and stripping to prepare a swelling termination tape for lithium batteries.

[0025] Preferably, in step S83, the modified polyurethane acrylate resin is dissolved in a solvent according to the mass fraction, and after the modified polyurethane acrylate resin is completely dissolved, the modified silicon dioxide is added and stirred evenly, and finally, the amino resin curing agent, the isocyanate curing agent and the sulfonic acid are respectively added and stirred evenly to obtain the electrolyte-resistant polyurethane acrylate glue;

[0026] Preferably, in steps S82 and S84, coating is performed at a speed of 7-25 m / min, and then the coating is dried in an oven at the same speed, and the temperatures of oven sections 1-8 are 40°C, 70°C, 90°C, 110°C, 130°C, 130°C, 140°C, and 110°C, respectively.

[0027] In summary, the present application includes at least one of the following beneficial technical effects:

[0028] 1. Simple preparation process: The swelling termination tape of the present invention adopts a simple coating and curing process, which is easy to realize large-scale production and reduce production costs.

[0029] 2. Strong high temperature resistance: The high temperature resistance of the swelling termination tape is improved by compounding modified polyurethane acrylate resin and modified silica, so that it can still maintain good performance in high temperature environment.

[0030] 3. High electrolyte resistance: The swelling termination tape of the present invention has excellent electrolyte resistance and can be immersed in the electrolyte for a long time without deformation or dissolution, thereby extending the service life of the lithium battery.

[0031] 4. High flame retardant performance: The swelling termination tape of the present invention has good flame retardant performance and can effectively prevent fire accidents of lithium batteries under abnormal conditions such as short circuit and overcharge.

[0032] 5. Enhance the impact resistance of lithium batteries: The swelling termination tape can maintain a certain strength and shape in three dimensions, effectively filling the gap between the battery cell and the shell, and preventing the shell and the battery cell from moving relative to each other when the lithium battery falls or is impacted, causing the battery to fail.

[0033] 6. Improve battery capacity and cycle performance: The swelling termination tape can fix and prevent the battery cells from loosening, increase battery capacity and rate, and improve battery cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings used in the embodiments:

[0035] Figure 1 This is a schematic diagram of the structure of the swelling termination tape for lithium batteries prepared in Example 6 of the present application;

[0036] In the figure, 1 represents a release agent coating; 2 represents a polyurethane swelling coating; 3 represents a PET film layer; 4 represents an electrolyte-resistant acrylic coating;

[0037] Figure 2 This is a product picture of the swelling termination tape for lithium batteries prepared in Example 6 of the present application. DETAILED DESCRIPTION

[0038] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0039] Preparation Example 1 Preparation of modified silicon dioxide

[0040] The preparation method of modified silicon dioxide comprises the following steps:

[0041] S71. Dissolve 80 g of succinic anhydride in 450 g of N,N-dimethylformamide solution according to mass fractions, add 180 g of γ-aminopropyltriethoxysilane, heat and stir at a water bath temperature of 73° C. for 2.5 hours to obtain a mixed solution A.

[0042] S72, dissolving 120 g of silicon dioxide having an average particle size of 10 nm in 500 g of N,N-dimethylformamide solution according to mass fractions to obtain a mixed solution B;

[0043] S73, adding the mixed solution B dropwise into the mixed solution A, and continuing to stir and react for 3 hours to obtain pretreated silica;

[0044] S74, the pretreated silica was mixed with 100 g of 2-methylimidazole and 80 g of zinc nitrate hexahydrate, and 1400 g of ethanol was added, and ultrasonic polymerization was performed in an 800 W water bath ultrasonic device for 3.5 hours. The obtained product was washed and dried to obtain modified silica.

[0045] Preparation Example 2 Preparation of modified polyurethane acrylate resin

[0046] The preparation method of the modified polyurethane acrylate resin is as follows: under nitrogen protection, 3.5 kg of polyether triol, 1.7 kg of polycaprolactone triol, 2.3 kg of hydroxyethyl methacrylate and 0.35 kg of dibutyltin dilaurate are mixed evenly, the temperature is raised to 55° C., 2.3 kg of isophorone diisocyanate is added and reacted for 3.5 hours, the temperature is then raised to 73° C., 0.36 kg of triphenyl phosphate is added and reacted for 2.5 hours to obtain the modified polyurethane acrylate resin.

[0047] The modified polyurethane acrylate resin prepared above was applied to Example 1-Example 6.

[0048] Example 1

[0049] A swelling termination tape for a lithium battery, the swelling termination tape comprising, from bottom to top, a release agent coating, a polyurethane swelling coating, a PET film layer and an electrolyte-resistant polyurethane acrylic coating, the release agent coating having a thickness of 0.5 μm, the polyurethane swelling coating having a thickness of 10 μm, the PET film layer having a thickness of 36 μm, and the electrolyte-resistant polyurethane acrylic coating having a thickness of 10 μm, wherein the electrolyte-resistant polyurethane acrylic coating, in parts by mass, is prepared from raw materials comprising: 55 kg of modified polyurethane acrylate resin, 0.5 kg of amino resin curing agent, 3 kg of toluene diisocyanate, 0.5 kg of sulfonic acid, and 55 kg of solvent, and the solvent, in parts by mass, comprises: 25 kg of isopropanol and 30 kg of N,N-dimethylformamide.

[0050] The method for preparing the swelling termination tape for lithium battery comprises the following steps:

[0051] S81, dissolving 8 kg of thermoplastic polyurethane resin in 8 kg of N,N-dimethylformamide, and after the thermoplastic polyurethane resin is completely dissolved, adding 0.8 kg of toluene diisocyanate, stirring evenly, to obtain polyurethane glue;

[0052] S82, applying polyurethane glue onto the PET film surface, and forming a polyurethane swelling coating on the PET film after drying, to obtain a PET film coated with the polyurethane swelling coating;

[0053] S83, dissolving the modified polyurethane acrylate resin in a solvent according to the mass fractions, and after the modified polyurethane acrylate resin is completely dissolved, respectively adding an amino resin curing agent, toluene diisocyanate and sulfonic acid, stirring evenly, to obtain an electrolyte-resistant polyurethane acrylate glue;

[0054] S84. Apply electrolyte-resistant polyurethane acrylic glue to the release surface of the PET single-sided silicon release film, and after drying, form an electrolyte-resistant polyurethane acrylic coating on the PET single-sided silicon release film, and then laminate the electrolyte-resistant polyurethane acrylic coating to the PET surface of the PET film coated with a polyurethane swelling coating. After lamination, apply a layer of non-silicone release agent on the polyurethane swelling coating surface, and after drying, peel off the PET single-sided silicon release film, and then perform aging and stripping to prepare a swelling termination tape for lithium batteries.

[0055] In steps S82 and S84, coating is carried out at a speed of 7 m / min, and then the surface of the coating is dried in the oven at the same speed. The temperatures of oven sections 1-8 are 40°C, 70°C, 90°C, 110°C, 130°C, 130°C, 140°C, and 110°C, respectively.

[0056] Example 2

[0057] A swelling termination tape for a lithium battery, the swelling termination tape comprising, from bottom to top, a release agent coating, a polyurethane swelling coating, a PET film layer and an electrolyte-resistant polyurethane acrylic coating, the release agent coating having a thickness of 1 μm, the polyurethane swelling coating having a thickness of 50 μm, the PET film layer having a thickness of 6 μm, and the electrolyte-resistant polyurethane acrylic coating having a thickness of 5 μm, wherein the electrolyte-resistant polyurethane acrylic coating, in parts by mass, is prepared from raw materials comprising: 130 kg of modified polyurethane acrylate resin, 3 kg of amino resin curing agent, 0.5 kg of diphenylmethane diisocyanate, 2 kg of sulfonic acid, and 140 kg of solvent, wherein the solvent, in parts by mass, comprises: 90 kg of isopropanol and 50 kg of N,N-dimethylformamide.

[0058] The method for preparing the swelling termination tape for lithium battery comprises the following steps:

[0059] S81, dissolving 8 kg of thermoplastic polyurethane resin in 8 kg of N,N-dimethylformamide, and after the thermoplastic polyurethane resin is completely dissolved, adding 0.8 kg of toluene diisocyanate, stirring evenly, to obtain polyurethane glue;

[0060] S82, applying polyurethane glue onto the PET film surface, and forming a polyurethane swelling coating on the PET film after drying, to obtain a PET film coated with the polyurethane swelling coating;

[0061] S83, dissolving the modified polyurethane acrylate resin in a solvent according to the mass fraction, and after the modified polyurethane acrylate resin is completely dissolved, respectively adding an amino resin curing agent, diphenylmethane diisocyanate and sulfonic acid, stirring evenly, to obtain an electrolyte-resistant polyurethane acrylate glue;

[0062] S84. Apply electrolyte-resistant polyurethane acrylic glue to the release surface of the PET single-sided silicon release film, and after drying, form an electrolyte-resistant polyurethane acrylic coating on the PET single-sided silicon release film, and then laminate the electrolyte-resistant polyurethane acrylic coating to the PET surface of the PET film coated with a polyurethane swelling coating. After lamination, apply a layer of non-silicone release agent on the polyurethane swelling coating surface, and after drying, peel off the PET single-sided silicon release film, and then perform aging and stripping to prepare a swelling termination tape for lithium batteries.

[0063] In steps S82 and S84, coating is carried out at a speed of 25 m / min, and then the surface of the coating is dried in the oven at the same speed. The temperatures of oven sections 1-8 are 40°C, 70°C, 90°C, 110°C, 130°C, 130°C, 140°C, and 110°C, respectively.

[0064] Example 3

[0065] A swelling termination tape for a lithium battery, the swelling termination tape comprising, from bottom to top, a release agent coating, a polyurethane swelling coating, a PET film layer and an electrolyte-resistant polyurethane acrylic coating, the release agent coating having a thickness of 0.8 μm, the polyurethane swelling coating having a thickness of 30 μm, the PET film layer having a thickness of 15 μm, and the electrolyte-resistant polyurethane acrylic coating having a thickness of 6 μm, wherein the electrolyte-resistant polyurethane acrylic coating, in parts by mass, is prepared from raw materials comprising: 90 kg of modified polyurethane acrylate resin, 1 kg of amino resin curing agent, 1.2 kg of toluene diisocyanate, 1 kg of sulfonic acid, and 95 kg of solvent, wherein the solvent, in parts by mass, comprises: 55 kg of isopropanol and 40 kg of N,N-dimethylformamide.

[0066] The method for preparing the swelling termination tape for lithium battery comprises the following steps:

[0067] S81, dissolving 8 kg of thermoplastic polyurethane resin in 8 kg of N,N-dimethylformamide, and after the thermoplastic polyurethane resin is completely dissolved, adding 0.8 kg of toluene diisocyanate, stirring evenly, to obtain polyurethane glue;

[0068] S82, applying polyurethane glue onto the PET film surface, and forming a polyurethane swelling coating on the PET film after drying, to obtain a PET film coated with the polyurethane swelling coating;

[0069] S83, dissolving the modified polyurethane acrylate resin in a solvent according to the mass fractions, and after the modified polyurethane acrylate resin is completely dissolved, respectively adding an amino resin curing agent, toluene diisocyanate and sulfonic acid, stirring evenly, to obtain an electrolyte-resistant polyurethane acrylate glue;

[0070] S84. Apply electrolyte-resistant polyurethane acrylic glue to the release surface of the PET single-sided silicon release film, and after drying, form an electrolyte-resistant polyurethane acrylic coating on the PET single-sided silicon release film, and then laminate the electrolyte-resistant polyurethane acrylic coating to the PET surface of the PET film coated with a polyurethane swelling coating. After lamination, apply a layer of non-silicone release agent on the polyurethane swelling coating surface, and after drying, peel off the PET single-sided silicon release film, and then perform aging and stripping to prepare a swelling termination tape for lithium batteries.

[0071] In steps S82 and S84, coating is carried out at a speed of 12 m / min, and then the surface of the coating is dried in the oven at the same speed. The temperatures of oven sections 1-8 are 40°C, 70°C, 90°C, 110°C, 130°C, 130°C, 140°C, and 110°C, respectively.

[0072] Example 4

[0073] A swelling termination tape for a lithium battery, the swelling termination tape comprising, from bottom to top, a release agent coating, a polyurethane swelling coating, a PET film layer and an electrolyte-resistant polyurethane acrylic coating, the release agent coating having a thickness of 0.8 μm, the polyurethane swelling coating having a thickness of 30 μm, the PET film layer having a thickness of 15 μm, and the electrolyte-resistant polyurethane acrylic coating having a thickness of 6 μm, wherein the electrolyte-resistant polyurethane acrylic coating, in parts by mass, comprises raw materials for preparation of 90 kg of modified polyurethane acrylate resin, 1 kg of amino resin curing agent, 1.2 kg of toluene diisocyanate, 1 kg of sulfonic acid, 5 kg of modified silicon dioxide, and 95 kg of solvent, wherein the solvent, in parts by mass, comprises 55 kg of isopropanol and 40 kg of N,N-dimethylformamide.

[0074] The method for preparing the swelling termination tape for lithium battery comprises the following steps:

[0075] S81, dissolving 8 kg of thermoplastic polyurethane resin in 8 kg of N,N-dimethylformamide, and after the thermoplastic polyurethane resin is completely dissolved, adding 0.8 kg of toluene diisocyanate, stirring evenly, to obtain polyurethane glue;

[0076] S82, applying polyurethane glue onto the PET film surface, and forming a polyurethane swelling coating on the PET film after drying, to obtain a PET film coated with the polyurethane swelling coating;

[0077] S83, dissolving the modified polyurethane acrylate resin in a solvent according to the mass fraction, adding the modified silicon dioxide after the modified polyurethane acrylate resin is completely dissolved, stirring evenly, and finally adding the amino resin curing agent, toluene diisocyanate and sulfonic acid respectively, stirring evenly, to obtain electrolyte resistant polyurethane acrylate glue;

[0078] S84. Apply electrolyte-resistant polyurethane acrylic glue to the release surface of the PET single-sided silicon release film, and after drying, form an electrolyte-resistant polyurethane acrylic coating on the PET single-sided silicon release film, and then laminate the electrolyte-resistant polyurethane acrylic coating to the PET surface of the PET film coated with a polyurethane swelling coating. After lamination, apply a layer of non-silicone release agent on the polyurethane swelling coating surface, and after drying, peel off the PET single-sided silicon release film, and then perform aging and stripping to prepare a swelling termination tape for lithium batteries.

[0079] In steps S82 and S84, coating is carried out at a speed of 12 m / min, and then the surface of the coating is dried in the oven at the same speed. The temperatures of oven sections 1-8 are 40°C, 70°C, 90°C, 110°C, 130°C, 130°C, 140°C, and 110°C, respectively.

[0080] Example 5

[0081] The same as Example 4, except that the amount of modified silica added is 6 kg.

[0082] Example 6

[0083] The same as Example 4, except that the amount of modified silicon dioxide added is 5.5 kg.

[0084] Comparative Example 1

[0085] The same as Example 6, except that an equal amount of silicon dioxide is used instead of modified silicon dioxide.

[0086] Performance testing

[0087] Test 1

[0088] Swelling and shape retention test of swelling termination tape: The swelling termination tapes for lithium batteries prepared in Examples 1 to 6 and Comparative Example 1 were cut into samples with a length of 55 mm and a width of 58 mm, respectively, and immersed in an electrolyte at 85° C. for 4 hours, and the swelling rate was measured and calculated, and the shape retention after swelling was observed; the electrolyte solute was 1 mol / L lithium perchlorate trihydrate, and the solvent was 1.2-propylene glycol carbonate and ethylene glycol dimethyl ether, with a weight ratio of 1:1;

[0089] Transverse swelling ratio = (width after immersion in electrolyte / 58) × 100%;

[0090] Longitudinal swelling rate = (length after immersion in electrolyte / 55) × 100%; the test results are shown in Table 1;

[0091] Test 2

[0092] Loop initial adhesion test: The lithium batteries prepared in Examples 1 to 6 and Comparative Example 1 were subjected to a loop initial adhesion test using swelling termination tapes. The test method was based on GB / T31125-2014. The test results are shown in Table 2.

[0093] Test 3

[0094] Bounce test: The lithium batteries prepared in Examples 1 to 6 and Comparative Example 1 were tested for bounce using swelling termination tape. The test method is as follows: The swelling termination tape was made into a 58mm wide roll, and the sample was placed in a winding device for cylindrical cell winding. Each cell used a tape with a width x length of 58mm x 54mm, and after winding, the cell was left to stand for 4 hours to observe whether it bounced. According to different forms, it can be divided into the following two states:

[0095] 1. The cylindrical battery cell remains unchanged and maintains its original shape;

[0096] 2. The cylindrical battery cell pops open, and the swelling termination glue is loosened from the battery cell; the test results are shown in Table 2;

[0097] Test 4

[0098] The lithium battery swelling termination tape prepared in Examples 1 to 6 and Comparative Example 1 is bonded to the bare battery cell of the lithium battery, which swells when immersed in the lithium battery electrolyte to fill the gap between the battery cell and the steel shell; the prepared lithium battery is subjected to battery roller performance evaluation, which is judged by evaluating the battery voltage, internal resistance and pole ear conditions under vibration environments such as long time, high frequency, large amplitude, or large impact; the specific method is: each group of tests uses 100 fully charged 4.2V cylindrical lithium batteries to be added to an octahedral prism, and after a fixed speed of 66RPM and continuous rotation for 100 minutes, if no power supply is detected or the internal resistance increases by more than 15%, it is determined that the battery roller performance is poor, and after disassembling the battery, if the battery pole ear is broken, it is determined that the performance of the swelling termination glue for the lithium battery is unqualified, and the test results are shown in Table 3.

[0099] Table 1 Swelling and shape retention ability test

[0100] project Transverse swelling rate / % Longitudinal swelling rate / % After swelling Example 1 1.15 1.16 Good shape retention Example 2 1.27 1.29 Good shape retention Example 3 1.22 1.21 Good shape retention Example 4 1.38 1.39 Excellent shape retention Example 5 1.39 1.38 Excellent shape retention Example 6 1.37 1.37 Excellent shape retention Comparative Example 1 1.18 1.16 Maintains shape, but strength is reduced

[0101] Table 2 Ring initial adhesion and spring-off test

[0102] project Ring initial adhesion / (N / 25mm) Cylindrical cell status Example 1 1.6 Cylindrical cells remain unchanged Example 2 1.7 Cylindrical cells remain unchanged Example 3 1.9 Cylindrical cells remain unchanged Example 4 2.5 Cylindrical cells remain unchanged Example 5 2.7 Cylindrical cells remain unchanged Example 6 2.6 Cylindrical cells remain unchanged Comparative Example 1 0.3 The swelling termination glue is slightly loose from the battery cell

[0103] Table 3 Battery roller performance evaluation

[0104] project Number of lithium battery drums with poor performance Number of broken lithium battery tabs Example 1 1 2 Example 2 2 1 Example 3 1 1 Example 4 0 0 Example 5 0 0 Example 6 0 0 Comparative Example 1 5 6

[0105] Analyzing the data in Tables 1, 2, and 3, we can see that:

[0106] 1) The swelling termination tape for lithium batteries prepared in Examples 4 to 6 has a simple preparation process, strong high temperature resistance and high electrolyte resistance, and can maintain a certain strength and shape in three dimensions by absorbing electrolyte to expand at a high rate, and will not fall off the battery cell, nor will it be dissolved and fall off by the electrolyte, and can fix and prevent the battery cell from loosening, increase the battery capacity, rate and improve the battery cycle performance. The swelling termination tape is applied to lithium batteries. In the stress resistance test of lithium batteries, it can effectively enhance the impact resistance of lithium batteries during daily use, and prevent the relative movement of the shell and the battery cell when the lithium battery falls or is impacted, thereby extending the service life of the lithium battery and the safety factor of use.

[0107] 2) The comparative analysis of the performance of the swelling termination tape for lithium batteries prepared in combination with Examples 3 and 4-6 shows that the addition of modified silica increases the adhesion between the electrolyte-resistant polyurethane acrylic coating and the PET film layer, prolongs the service life of the swelling termination tape, and ensures that no residual glue will remain when the swelling termination tape is removed. Modified silica increases the affinity of silica to organic materials, enhances the strength, toughness, high temperature resistance and electrolyte resistance of the swelling termination tape. Improving adsorption performance: Compounding modified polyurethane acrylate resin with modified silica improves the adsorption performance of the tape, solving the technical problem that the existing swelling adhesive has poor temperature resistance and poor expansion effect in high-temperature electrolyte. Enhanced lithium battery performance: The use of modified silica makes the swelling termination tape have better electrolyte and high temperature resistance, forming a three-dimensional structure with a certain strength, effectively filling the gap between the battery cell and the shell, and improving the impact resistance of the lithium battery. It prevents the relative movement of the shell and the battery cell when the lithium battery falls or is impacted, which may cause the battery to fail, thereby extending the service life of the lithium battery and the safety factor of use.

[0108] 3) The comparative analysis of the performance of the swelling termination tape for lithium batteries prepared in Example 6 and Comparative Example 1 shows that the surface of unmodified silica contains hydroxyl groups, which easily absorbs moisture in the air. When applied to organic materials, phase separation often occurs, which affects the overall performance of the swelling termination tape.

[0109] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A swelling termination tape for lithium batteries, characterized in that: The swelling termination tape comprises, from bottom to top, a release agent coating, a polyurethane swelling coating, a PET film layer and an electrolyte-resistant polyurethane acrylic coating, wherein the release agent coating has a thickness of 0.5-1 μm, the polyurethane swelling coating has a thickness of 10-50 μm, the PET film layer has a thickness of 6-36 μm, and the electrolyte-resistant polyurethane acrylic coating has a thickness of 2-10 μm, wherein the electrolyte-resistant polyurethane acrylic coating is prepared from raw materials, by weight, comprising: 55-130 parts of modified polyurethane acrylate resin, 0.5-3 parts of amino resin curing agent, 0.5-5 parts of isocyanate curing agent, 0.5-2 parts of sulfonic acid, 55-140 parts of solvent, and 5-6 parts of modified silicon dioxide; The preparation method of the modified polyurethane acrylate resin is as follows: under nitrogen protection, polyether triol, polycaprolactone triol, hydroxyethyl methacrylate and dibutyltin dilaurate are uniformly mixed, the temperature is raised to 50-60° C., isophorone diisocyanate is added and reacted for 3-4 hours, and the temperature is raised to 70-75° C., triphenyl phosphate is added and reacted for 2-3 hours to obtain the modified polyurethane acrylate resin; The mass ratio of the polyether triol, polycaprolactone triol, hydroxyethyl methacrylate, dibutyltin dilaurate, isophorone diisocyanate and triphenyl phosphate is 35:17:23:3.5:23:3.6; The preparation method of the modified silicon dioxide comprises the following steps: S71. Dissolve 8 parts of succinic anhydride in 40-50 parts of N,N-dimethylformamide solution according to mass fractions, add 18 parts of γ-aminopropyltriethoxysilane, heat and stir at a water bath temperature of 73° C. for 2-3 hours to obtain a mixed solution A. S72, dissolving 12 parts by mass of silicon dioxide having an average particle size of 10 nm in 50 parts of N,N-dimethylformamide solution to obtain a mixed solution B; S73, adding the mixed solution B dropwise into the mixed solution A, and continuing to stir and react for 3 hours to obtain pretreated silica; S74, mixing the pretreated silica with 10 parts of 2-methylimidazole and 8 parts of zinc nitrate hexahydrate, adding 140 parts of ethanol, and ultrasonically polymerizing in an 800 W water bath ultrasonic device for 3-4 hours, washing and drying the obtained product to obtain modified silica.

2. A swelling termination tape for lithium batteries according to claim 1, characterized in that: The isocyanate curing agent is at least one of toluene diisocyanate and diphenylmethane diisocyanate.

3. The swelling termination tape for lithium battery according to claim 1, characterized in that: The solvent, calculated by weight, includes: 25-90 parts of isopropanol and 30-50 parts of N,N-dimethylformamide.

4. A method for preparing a swelling termination tape for a lithium battery as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S91, dissolving 8 kg of thermoplastic polyurethane resin in 8 kg of N,N-dimethylformamide, and after the thermoplastic polyurethane resin is completely dissolved, adding 0.8 kg of toluene diisocyanate, stirring evenly, to obtain polyurethane glue; S92, applying polyurethane glue onto the PET film surface, and forming a polyurethane swelling coating on the PET film after drying, to obtain a PET film coated with the polyurethane swelling coating; S93, dissolving the modified polyurethane acrylate resin in a solvent according to the mass fraction, adding the modified silicon dioxide after the modified polyurethane acrylate resin is completely dissolved, stirring evenly, and finally adding the amino resin curing agent, isocyanate curing agent and sulfonic acid respectively, stirring evenly, to obtain electrolyte resistant polyurethane acrylic glue; S94. Apply electrolyte-resistant polyurethane acrylic glue to the release surface of the PET single-sided silicon release film, and after drying, form an electrolyte-resistant polyurethane acrylic coating on the PET single-sided silicon release film, and then laminate the electrolyte-resistant polyurethane acrylic coating to the PET surface of the PET film coated with a polyurethane swelling coating. After laminating, apply a layer of non-silicone release agent on the polyurethane swelling coating surface, and after drying, peel off the PET single-sided silicon release film, and then perform aging and stripping to prepare a swelling termination tape for lithium batteries.

5. A swelling termination tape for lithium batteries according to claim 4, characterized in that: In steps S92 and S94, coating is carried out at a speed of 7-25 m / min, and then the surface of the film enters the oven for drying at the same speed. The temperatures of sections 1-8 of the oven are 40°C, 70°C, 90°C, 110°C, 130°C, 130°C, 140°C, and 110°C, respectively.

Citation Information

Patent Citations

  • Preparation method of ZIF-8-SiO2 hybridized fixed phase

    CN106732472A

  • Elastomer material for shoe sole and preparation method of elastomer material

    CN118165209A

Cited By

  • High-temperature-resistant anti-warping termination adhesive tape and preparation method thereof

    CN121379405A